Urease de proteus mirabilis : concepção e avaliação de peptídeos inibidores da atividade não-enzimática das ureases - Caruso, Paula Bacaicoa (2021)
Ureases are metalloenzymes that catalyze the hydrolysis of urea in ammonia and carbon dioxide. Acting non-enzymatically, ureases are capable of promoting the activation of several cell types in mammals, like platelets and neutrophils, have a proinflammatory action, and some are neurotoxic to rodents. For several microorganisms, ureases play an important role as virulence factors, for example, for the bacteria Helicobacter pylori and Proteus mirabilis. Currently, there are no urease inhibitors with therapeutic applications available on the market, and those already tested cause multiple undesirable effects. Also, urease inhibitors have until then been designed to inhibit ureolytic activity and are probably inefficient to block their non-enzymatic effects. The Proteus mirabilis Urease (PMU) was the focus for the design of the inhibitory peptides planned in this study. Twentyseven potentially urease-inhibiting peptides were planned, two of which were synthesized and tested. As a reference for the formulation of the ligand, the interaction of accessory protein D (PMU-UreD) with the PMU-beta subunit (PMU-UreB) was analyzed, identifying the amino acid residues present in this region, as well as their equivalents in Helicobacter pylori Urease (HPU) and Klebsiella aerogenes Urease (KAU) structures. The peptides, designated 1 and 2, were tested in HEK293 cells treated with PMU. Both peptides, at a 3- fold molar ratio to PMU, inhibited the effect of urease at a dose of 126 nM to induce the release of the TNF-α cytokine. Both also inhibited, in the same dose, the production of intracellular reactive oxygen species (ROS), within 6 h of treatment with PMU, and inhibitor 1 also promoted a significant decrease in ROS after 24 h. The results of this study confirmed the hypothesis that PMU B subunit ligands may interfere with ureases proinflammatory activity and that the formulated peptides have potential as prototypes of inhibitors of nonenzymatic activities of ureases. It is expected, in the future, that inhibitory peptides such as those conceived here may serve as a basis for the development of drugs capable of helping to combat diseases caused by urease-producing microorganisms.